Xenogeneic Mesenchymal Stem Cells in the Formation of Hyaline Cartilage in Osteochondral Goat Failure - Silva, Laís Meireles Costa; Rocha, Mariá Andrade de Carvalho; Nunes, Marllos Henrique Vieira; Medeiros, Brenda Lurian do Nascimento; Leite, Yulla Klinger de Carvalho; Rodrigues, Huanna Waleska Soares; Rodrigues, Marcelo Campos; Neto, Hermínio José da Rocha; Carvalho, Maria Acelina Martins de; Neto, Napoleão Martins Argôlo (Acta Scientiae Veterinariae, 2018)
Background: Osteochondral knee failures are among the most common causes of disability among the elderly human population and animal athletes. The xenogeneic transplantation of mesenchymal stem cells is a questionable therapeutic alternative that, despite the low expression of Major Histocompatibility Complex type II by these cells, still has relevant uncertainties about the safety and clinical efficacy. The main objective of the present study was to investigate whether the xenogeneic transplantation of mesenchymal stem cells induces hyaline cartilage formation, without histopathological evidence of rejection, in osteochondral failures of goats. Materials, Methods & Results: Five female goats were used, submitted to three surgical osteocondral failures in the right knee, treated with xenogenic mesenchymal stem cells of dental pulp, xenogenic platelet-rich plasma and hemostatic sponge of hydrolyzed collagen, respectively. The lesions were evaluated after 60 days of treatment, aiming to identify the presence of hyaline cartilage or fibrocartilage and the subchondral bone pattern (regenerated or disorganized). Transplantation of xenogenic mesenchymal stem cells induced predominant formation of hyaline cartilage (P < 0.05), with no histopathological evidence of inflammation when compared to the other treatments. Therapies with xenogeneic platelet-rich plasma and hemostatic sponge of hydrolyzed collagen induced greater formation of fibrocartilaginous cartilage, with no significant difference between them (P > 0.05). Macroscopically, the lesions of the stem cell treated group showed formation of firm repair tissue, opaque staining, integrated with adjacent cartilage and with the failure filling almost completely. The groups treated with PRP and hemostatic sponge of hydrolyzed collagen presented, on average, partial filling of the lesion, with irregular shape and darkened coloration. Discussion. The absence of macroscopic and histopathological evidences of an inflammatory process on the surface and in the internal portion of the osteochondral lesions treated with xenogeneic stem cells, probably due to the low expression of Major Histocompatibility Complex type II by these cells, which would theoretically induce low rejection response. Such observations are of great importance, since graft-versus- host disease syndrome is a serious condition, responsible for the low therapeutic efficacy with transplantation of cells or grafts in humans. The formation of fibrocartilage, although without macro and microscopic evidence of degeneration or necrosis, in the osteochondral failures treated with PRP and hemostatic collagen sponge suggest that paracrine factors of the local microenvironment of the osteochondral failure are possibly responsible for the formation of fibrocartilaginous tissue or by inhibition of normal cartilage formation. The fibrocartilage formed in the Plasma and Control groups, contributed to the commitment in the filling of the lesion, contrasting with the almost complete fill of the lesions treated with stem cells. The xenotransplantation of mesenchymal stem cells induced formation of hyaline cartilage and did not promote histopathological evidence of rejection in osteochondral lesions of goat knees. The treatments with PRP and hemostatic sponge of hydrolyzed collagen induced greater formation of fibrocartilaginous cartilaginous surface in the osteochondral failures.